Satisfação e sobrecarga de trabalho e sua relação com o sofrimento psíquico de profissionais de saúde mental na pandemia COVID-19 - Pinto, Debora Maria Salimon (2023)
Objective: To assess the general health, job satisfaction and work overload of professionals who worked in psychosocial care centers during COVID-19 and to analyze the influence of job satisfaction and work overload on the general health of these professionals. Methods: Correlational study developed with workers from psychosocial care centers in an inland city of São Paulo State: one CAPS alcohol and drugs III, one CAPS alcohol and drugs II, three CAPS children and two CAPS II adults. The population consisted of all professionals who worked in the direct care of the users (n=98). The established inclusion criteria were: being a worker with an employment contract with the sponsoring entity, working in the service for a minimum of six months and voluntarily accepting to participate in the study. Workers who did not perform direct care activities with patients (administrative agents, cleaning assistants, cooks and security guards) or were on vacation or sick leave were excluded. The non-probabilistic convenience sample consisted of 53 professionals (response rate: 54.08% of the population): nurses (n=11 – 73.3%), physicians (n=9 – 52.9%), social workers (n=4 – 57.1%), psychologists (n=13 – 65%), speech therapists (n=2 – 66.6%), physical educator (n=1 – 100%), occupational therapists (n=2 – 40%), nursing technicians and assistants (n=4 – 25%) and workshop assistants (n=7 – 58.3%). For data collection, the following instruments were used: sociodemographic characterization, impact (IMPACTO-BR) and satisfaction (SATIS-BR) assessment scales for professionals in mental health services, and the General Health Questionnaire (GHQ-12). Results: The overall satisfaction of CAPS professionals was moderate (3.67±0.45). When analyzing the subscales, the relationship with colleagues (subscale 4) reached the best evaluation (4.01±0.60), and working conditions (subscale 3) obtained the lowest average (3.42±0.57). The professional overload of CAPS workers was mild, with a global score of 1.82±0.63. Considering the subscales, the lowest burden fell on the physical and mental health of professionals, and the highest burden was on emotional repercussions, such as frustration, tiredness, depressive symptoms, and stress. Regarding the general health of the professionals, the average GHQ-12 score was 1.87±2.20, median was 1 and minimum and maximum values were 0 and 8 points, respectively. A significant portion of the sample, 17/53 (32.07%), had a score equal to or greater than three points, indicating the presence of psychological distress that deserves attention. The questions with the highest scores were about the ability to maintain attention in activities and about the feeling of being constantly tense and nervous. The multiple linear regression analysis showed that individuals with high workloads are 1.39 times more likely to present psychological distress, and those with low job satisfaction are 1.23 times more likely to present psychological distress. Conclusions: Professionals who worked in psychosocial care centers during COVID-19 had low work overload and moderate job satisfaction. High work overload and low job satisfaction were predictors of psychological distress. This evidence emphasizes the need for more significant investment in promoting professionals’ resilience and quality of life at work, including reducing the harmful effects of epidemic/pandemic outbreaks.